2023
DOI: 10.1186/s12967-023-04590-w
|View full text |Cite
|
Sign up to set email alerts
|

Matrix stiffness induces Drp1-mediated mitochondrial fission through Piezo1 mechanotransduction in human intervertebral disc degeneration

Wencan Ke,
Bingjin Wang,
Zhiwei Liao
et al.

Abstract: Background Extracellular matrix stiffness is emerging as a crucial mechanical cue that drives the progression of various diseases, such as cancer, fibrosis, and inflammation. The matrix stiffness of the nucleus pulposus (NP) tissues increase gradually during intervertebral disc degeneration (IDD), while the mechanism through which NP cells sense and react to matrix stiffness remains unclear. In addition, mitochondrial dynamics play a key role in various cellular functions. An in-depth investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…This self-amplifying loop between periostin and NF-kB can be triggered by Piezo1 activation, resulting in IDD 59 . Besides, Ke et al also identified that Piezo1 activation by matrix stiffness promotes NP cell apoptosis via activating the ERK1/2 pathway 145 . Piezo1-mediated iron overload disrupts iron metabolism and exacerbates ferroptosis in NP cells.…”
Section: Piezo1 In Musculoskeletal Physiologymentioning
confidence: 99%
“…This self-amplifying loop between periostin and NF-kB can be triggered by Piezo1 activation, resulting in IDD 59 . Besides, Ke et al also identified that Piezo1 activation by matrix stiffness promotes NP cell apoptosis via activating the ERK1/2 pathway 145 . Piezo1-mediated iron overload disrupts iron metabolism and exacerbates ferroptosis in NP cells.…”
Section: Piezo1 In Musculoskeletal Physiologymentioning
confidence: 99%